Low-loss fiber-to-chip couplers with ultrawide optical bandwidth - H. Gehring; M. Blaicher; W. Hartmann; P. Varytis; K. Busch; M. Wegener; W. H. P. Pernice (APL Photonics, 2019)
Providing efficient access from optical fibers to on-chip photonic systems is a key challenge for integrated optics. In general, current solutions allow either narrowband out-of-plane-coupling to a large number of devices or broadband edge-coupling to a limited number of devices. Here we present a hybrid approach using 3D direct laser writing, merging the advantages of both concepts and enabling broadband and low-loss coupling to waveguide devices from the top. In the telecom wavelength regime, we demonstrate a coupling loss of less than −1.8 dB between 1480 nm and 1620 nm. In the wavelength range between 730 nm and 1700 nm, we achieve coupling efficiency well above −8 dB which is sufficient for a range of broadband applications spanning more than an octave. The 3D couplers allow relaxed mechanical alignment with respect to optical fibers, with −1 dB alignment tolerance of about 5 µm in x- and y-directions and −1 dB alignment tolerance in the z-direction of 34 µm. Using automatized alignment, many such couplers can be connected to integrated photonic circuits for rapid prototyping and hybrid integration.